Changes in phosphorus mobilization and community assembly of bacterial and fungal communities in rice rhizosphere under phosphate deficiency - Sun, Ruibo; Zhang, Wenjie; Liu, Yangbing; Yun, Wenjing; Luo, Bingbing; Chai, Rushan; Zhang, Chaochun; Xiang, Xingjia; Su, Xiaofeng (Frontiers in Microbiology, 2022)
Rhizosphere microorganisms are closely associated with phosphorus (P) uptake in plants and are considered potential agents to mitigate P shortage. However, the mechanisms of rhizospheric microbial community assembly under P deficiency have yet to be elucidated. In this study, bacterial and fungal communities in rice rhizosphere and their P-mobilization potential under high (+P) and low (-P) concentrations of P were investigated. Microbial P-solubilizing capacity was significantly higher in -P treatment compared with that in +P treatment. Both bacterial and fungal P-mobilizing taxa were enriched in -P treatment; however, the proportion of P-mobilizing agents in the fungal community was markedly greater than that in the bacterial community. In addition, -P treatment lowered bacterial diversity in rice rhizosphere but increased fungal diversity. Further analysis demonstrated that the contribution of deterministic processes in governing bacterial community assembly was strengthened under P deficiency but was largely weakened in shaping the fungal community. These results highlighted that enriching P-mobilizing microbes in the rhizosphere is a vital way for rice to cope with P deficiency, and that fungi contribute considerably to P mobilization in rice rhizosphere. Findings from the study provide novel insights into the assembly of the rhizosphere microbiome under P deficiency and this will facilitate the development of rhizosphere microbial regulation strategies to increase nutrient uptake in plants.